Tyrosinase Expression during Neuroblast Divisions Affects Later Pathfinding by Retinal Ganglion Cells - Cronin, Carolyn A. (J Neurosci, 2003)
Occulocutaneous albinism is caused by mutations in the gene encoding the enzyme tyrosinase. Individuals with this disorder are predisposed to visual system deficits. We determined the critical period during development when tyrosinase expression is essential for the appropriate pathfinding of ganglion cell axons from the retina to the dorsal lateral geniculate nucleus. We used a line of mice with a Tyrosinase transgene, the expression of which is regulatable with the lac operator-repressor system, to restrict tyrosinase activity to discrete periods of embryogenesis. When tyrosinase was expressed throughout the period of neuroblast divisions that produce the ipsilaterally projecting ganglion cells, axonal projections innervated the same volume of the ipsilateral dorsal lateral geniculate nucleus of the thalamus as in normal mice. If tyrosinase expression ceased before the end of neuroblast divisions, or was not initiated until after they had begun, the degree of ipsilateral innervation was smaller, as in albino mice. Tyrosinase expression was not required during the entire period of pathfinding itself or during final maturation of the retinogeniculate pathway. Thus, tyrosinase appears to set up a signal early in visual system development that determines the pathway taken later by ganglion cell axons.